Histoenzymological and ultrastructural changes in lateral muscle fibers of Oreochromis niloticus (Teleostei: Cichlidae) after local injection of veratrine - Silva Freitas, Erika Maria; Dal Pai Silva, Maeli [UNESP]; Da Cruz-Höfling, Maria Alice (Springer Nature, 2001)
The effects of veratrine have been investigated in mammalian, amphibian, and crustacean muscle, but not in fish. In this work, the action of veratrine was studied in the lateral muscle of the freshwater teleost Oreochromis niloticus after intramuscular injection. Histoenzymological typing and electron microscopy of muscle fibers before and 15, 30, and 60 min after veratrine injection (10 ng/kg fish) were used to indirectly assess the morphological changes and the oxidative and m-ATPase activities. In some cases, muscles were pretreated with tetrodotoxin to determine whether the ultrastructural changes were the result of Na+ channel activation by veratrine. Veratrine altered the metabolism of fibers mainly after 30 min. Oxidative fibers showed decreased NADH-TR activity, whereas that of glycolytic and oxidative-glycolytic type fibers increased. There was no change in the m-ATPase activity of the three fiber types, except at 60 min postveratrine, when a novel fiber type, which showed no reversal after acidic and alkaline preincubations, appeared. Ultrastructural damage involved sarcomeres, myofibrils, and mitochondria, but the T-tubules remained intact. Pretreatment with tetrodotoxin (1 ng/ml) prevented the ultrastructural changes caused by veratrine. These results show that in fish skeletal muscle veratrine produces some effects that are not seen in mammalian muscle.
Keywords: Fish; Histoenzymology; Muscle plasticity; Ultrastructural changes; Veratrine; cevadine; myosin adenosine triphosphatase; sodium channel; tetrazolium reductase; tetrodotoxin; animal tissue; cell damage; cell ultrastructure; controlled study; electron microscopy; enzyme activity; fast muscle; mitochondrion; muscle cell; muscle fibril; muscle metabolism; nonhuman; priority journal; sarcomere; skeletal muscle; slow muscle; teleost; transverse tubular system; Adenosine Triphosphatases; Cichlids; Drug Antagonism; Injections, Intramuscular; Microscopy, Electron; Mitochondria, Muscle; Muscle Fibers, Fast-Twitch; Muscle Fibers, Slow-Twitch; Muscle, Skeletal; Sarcomeres; Tetrodotoxin; Amphibia; Animalia; Cichlidae; Crustacea; Mammalia; Oreochromis; Oreochromis niloticus; Teleostei